Lao People's Democratic Republic Nam Theun 2 Multipurpose Project : Reports 21A and 21B of the International Environmental and Social Panel of Experts - McDowell, David (World Bank, Washington, DC, 2014)
This report details seven recommendations from the International Environmental and Social Panel of Experts for the Nam Theun 2 (NT2) Multipurpose Project in the Lao People s Democratic Republic. 1) Watershed Management and Protection Authority (WMPA) conservation patrols will be repeated at least once a month, including the wet season. 2) The provincial and central government authorities will take effective action to recognize and halt the undermining of village authorities in the Nakai Nam Theun National Protected Area (NPA) for the illegal rosewood trade, including its participants, supporters, and enablers. 3) The WMPA will assure that law enforcement staff is provided at least two reliable, functional vehicles, a boat with good motor, motorbikes and laptops. 4) The organizations responsible for monitoring, patrolling and enforcing management of the reservoir, especially the WMPA and the resettlement-based village fisher groups, will find or develop mechanisms to complement and harmonize their activities to achieve effective management of the reservoir and its fishery. 5) The WMPA will develop rigorous criteria for evaluating which existing WMPA staff meets the present requirements and which do not, and to seek to replace the latter with university graduates or experienced staff from conservation organizations. 6) An institutional review of the WMPA and relevant line agencies will be carried out to consider the functions that the WMPA should implement in accordance with Decree 471. 7) The WMPA will monitor track construction in the NPA, only allow tracks that are in the agreed upon access plan, and actively halt and as appropriate destroy any other track construction.